Side Effects of Dental Metal Implants: Impact on Human Health (Metal as a Risk Factor of Implantologic Treatment) - Přikrylová, Jana; Procházková, Jarmila; Podzimek, Štěpán (BioMed research international, 2019)
Dental implants are often made of titanium alloys. Implant therapy currently promises a good long-term result without impacting health; however, its success depends on many factors. In this article, the authors focus on the most common risk factors associated with metallic surgical implants. Titanium-induced hypersensitivity can lead to symptoms of implant rejection. Corrosion and biofilm formation are additional situations in which these symptoms may occur. For medical purposes, it is important to define and discuss the characteristics of metals used in implantable devices and to ensure their biocompatibility. To avoid hypersensitivity reactions to metallic dental implants, precautionary principles for primary prevention should be established.
Keywords: Metals; Humans; Dental Implants; zubní implantáty; rizikové faktory; zubní slitiny; Dental Alloys; Titanium; koroze; Biocompatible Materials; biokompatibilní materiály; kovy; Risk Factors; Corrosion; lidé; titan